Motivasi Pembelajaran Blended Learning terhadap Mental Belajar Siswa - Alya Azzahra Furqon; Uus Ruswandi; Oban Sobandi (Gunung Djati Conference Series, 2022)
Application of  blended learning during  Covid-19 period was implemented in almost all educational institutions, including at MAN Purwakarta. In its application, there are several problems, like: 1) there are some students who attend online learning only to fill out the attendance list; 2) some students are not on time in collecting assignments. This is because teachers and students are still in the process of adapting to blended learning. This study aimed to determine the effect of blended learning motivation on students mental learning in the subjects of Fiqh, the material of Syara's law, and its distribution in class XII of MAN Purwakarta. This study uses the correlational associative method to determine the effect of variable X motivation on variable Y students mental learning. The results of the research are: 1) students' learning motivation in class XII MAN Purwakarta is in the high category with a score of 3,96; 2) their mental learning are in the moderate category with a score of 3,40; and 3) there is an influence between variable X on variable Y by 31%, and the remaining 69% is influenced by other factors.